Physicochemical study of poly(ether ether ketone) electrolyte membranes sulfonated with mixtures of fuming sulfuric acid and sulfuric acid for direct methanol fuel cell application - Jaafar, Jaafariah (Elsevier B.V., 2007)
Sulfonated poly(ether ether ketone) (SPEEK) membranes with various degrees of sulfonation (DS) have been prepared as a potential membrane material for proton exchange membrane by sulfonation process using mixtures of (15–30% concentration) fuming sulfuric acid and (95–98%) concentrated sulfuric acid as the sulfonating agent. The sulfonation process was conducted at room temperature by varying the acid ratio and reaction time. The produced membranes were then characterized by evaluating the ion exchange capacity (IEC), water uptake, thermal stability, proton conductivity and methanol permeability as a function of degree of sulfonation. The proton conductivity of the sulfonated PEEK membranes with various DS was within the magnitude of 10−3 and 10−2 S cm−1 at room temperature and the methanol permeability was in the range of 3.45×10−7 to 2.73×10−6 cm2 s−1. The overall membrane performance of the SPEEK membrane with 80% DS was six times higher than Nafion membrane. In conclusion, the SPEEK membrane produced was acceptable and stable enough within the temperature range of direct methanol fuel cell (DMFC) application